Age-related calcium signaling disturbance restricted cAMP metabolism and induced ovarian oxidation stress in laying ducks - Cheng-long Jin; Sheng-lin Wang; Shuang Wang; Ya-nan Zhang; Wei-guang Xia; Chang Zhang; Xue-bing Huang; Kai-chao Li; Chun-tian Zheng; Wei Chen (Poultry Science)
The ovary is the main controller of female fertility, unfortunately, its onset of aging processes was earlier than other organs. Our previous studies showed calcium (Ca) deficiency reduced ovarian weight and declined numbers of dominant follicles in an avian model. However, whether Ca provided a functional role in follicle development of aged avian, and its further mechanism was still unknown. In this study, fifty180-day-old and fifty 700-day-old female Longyan ducks were divided into the young group and the aged group to illustrate the differences of Ca signaling and further mechanisms. We found the poor productive performance of aged ducks was correlated with follicle decreased numbers and atrophied microstructure, and restricted antioxidant ability of granulosa cells (GCs). Then, according to RNA-Seq analysis, we detected those aged ducks displayed lower Ca concentration in the ovary, while Ca channel related gene expression was increased in GCs to maintain homeostasis. Moreover, the cyclic adenosine monophosphate (cAMP) concentration and cAMP synthase family related genes were also decreased in GCs of aged ducks. Fortunately, medium supplemented with Ca channel-activator A23187 enhanced GC viability, antioxidant ability, tight junction ability, and increased cAMP concentration by improved cAMP metabolism, otherwise, the opposite changes were observed with Ca2+-chelating agent EGTA or Ca channel-inhibitor Verapamil supplementation. In conclusion, aging disordered Ca signaling to limit cAMP metabolism, then decreased antioxidant ability and inhibited proliferation and migration ability of GCs. Thus, the follicle development and reproductive performance were restricted in aged avian.